Helicteres isora L: regeneration through meristem culture - Deshpande, Harshal A.; Bhalsing, Sanjivani R. (Acta Biologica Szegediensis, 2015)
Helicteres isora Linn (Sterculiaceae) is an endangered plant species of medicinal importance. Rapid regeneration of this plant was achieved via shoot tip explants with highest response of shoot induction (100%) on MS basal medium supplemented with 12 μM 6-ben-zylaminopurine (BAP) and 16 μM kinetin (Kin) alone. This combination of phytohormones was found suitable for complete plant regeneration through meristem culture. The developed method can be successfully employed for large-scale regeneration and conservation of this medicinal plant.